2014
DOI: 10.5194/acp-14-2219-2014
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric mercury speciation and mercury in snow over time at Alert, Canada

Abstract: Abstract. Ten years of atmospheric mercury speciation data and 14 years of mercury in snow data from Alert, Nunavut, Canada, are examined. The speciation data, collected from 2002 to 2011, includes gaseous elemental mercury (GEM), particulate mercury (PHg) and reactive gaseous mercury (RGM). During the winter-spring period of atmospheric mercury depletion events (AMDEs), when GEM is close to being completely depleted from the air, the concentration of both PHg and RGM rise significantly. During this period, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 69 publications
(92 reference statements)
11
70
0
Order By: Relevance
“…In addition, Toyota et al (2014) provided the temperature dependence of these reactions, which needs to be verified experimentally. Based on 10 years of data, Steffen et al (2014) also reported higher levels of mercury in the snow when the atmospheric conditions favored the formation of RGM. This springtime shift from the predominance of Hg(p) to RGM in AMDEs likely directly impacts the amount of mercury deposited onto the snowpack.…”
Section: Springtime Amdesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Toyota et al (2014) provided the temperature dependence of these reactions, which needs to be verified experimentally. Based on 10 years of data, Steffen et al (2014) also reported higher levels of mercury in the snow when the atmospheric conditions favored the formation of RGM. This springtime shift from the predominance of Hg(p) to RGM in AMDEs likely directly impacts the amount of mercury deposited onto the snowpack.…”
Section: Springtime Amdesmentioning
confidence: 99%
“…This shift has already been evidenced at Churchill, Manitoba (Kirk et al, 2006), ALT (Cobbett et al, 2007), and NYA (Steen et al, 2011) and has been shown to repeat year after year at ALT . Steffen et al (2014) suggested that this shift is due to temperature and particle availability. Using a detailed air-snowpack model for interactions of bromine, ozone, and mercury in the springtime Arctic, Toyota et al (2014) proposed that Hg(p) is mainly produced as HgBr 2− 4 through uptake of RGM into bromine-enriched aerosols after ozone is significantly depleted in the air mass.…”
Section: Springtime Amdesmentioning
confidence: 99%
“…The nearby Lincoln Sea typically remains frozen year-round. The aerosol number size distribution in the range of 10 to 500 nm is measured with a TSI 3034 SMPS that is calibrated on site (Leaitch et al, 2013;Steffen et al, 2014).…”
Section: Measurement Sites and Instrumentationmentioning
confidence: 99%
“…In our study, we did not have sufficient temporal resolution of snow sampling during the period of AMDEs to closely track the fate of Hg deposition during AMDEs and subsequent re-emissions. However, we find that snow Hg enhancements during AMDEs were much lower than at coastal sites (e.g., Steffen et al, 2014), but a coarse temporal sampling could just have missed peak snow Hg levels at this site. We also found that after AMDEs, snow Hg diss in surface snow declined to levels as was observed prior to AMDEs, and no concentration enhancements were observed deeper in the snowpack.…”
Section: Seasonal Patternsmentioning
confidence: 59%
“…The lack of consistent statistically significant associations between major ions and Hg diss across the entire snowpack depth (Table 2a) further suggests that initial snowfall Hg content was maintained and largely unaltered after deposition, with no clear accumulation or depletion zones as found in other snowpacks (Ferrari et al, 2005;Poulain et al, 2004;Steffen et al, 2014). We found a small relative enrichment of alkaline earth elements in snowpack samples compared to surface snow, which indicates some additional contributions of local mineral dust, yet this did not result in a measurable increase in snowpack Hg levels.…”
Section: Cation and Anion Concentrationsmentioning
confidence: 99%